Study of signal transduction factors involved in mycoparasitic response of Trichoderma atroviride - Scala V; Zeilinger S; Ambrosino P; Brunner K; Reithner B; Mach R L; Woo S L; Cristilli M; Scala F; Lorito M (浙江大学学报. 农业与生命科学版)
Numerous Trichoderma spp. are mycoparasites and commercially applied as biological control agents against a large number of plant pathogenic fungi. The mycoparasitic interaction is host-specific and several research strategies have been applied to identify the main genes and compounds involved in the antagonist-plant-pathogen three-way interaction. During mycoparasitism, signals from the host fungus are recognised by Trichoderma, stimulating antifungal activities that are accompanied by morphological changes and the secretion of hydrolytic enzymes and antibiotics. Interestingly some morphological changes appeared highly conserved in the strategy of pathogenicity within the fungal world, i. e. the formation of appressoria as well as the secretion of hydrolytic enzymes seem to be general mechanisms of attack both for plant pathogens and mycoparasitic antagonists. This knowledge is being used to identify receptors and key components of signalling pathways involved in fungus-fungus interaction. For this purpose we have cloned the first genes (tmk1, tga1, tga3) from T. atroviride showing a high similarity to MAP kinase and G protein subunits (see abstract by Zeilinger et al.), which have been found to have an important role in pathogenicity by Magnaporthe grisea. To identify the function and involvement of these factors in mycoparasitism by T. atroviride, tmk1, tga1, tga3 disruptant strains were produced. The knock-out mutants were tested by in vivo biocontrol assays for their ability to inhibit soil and foliar plant pathogens such as Rhizoctonia solani, Pythium ultimum and Botrytis cinerea. Disruption of these genes corresponded to a complete loss of biocontrol ability, suggesting a significant role in mycoparasitism. In particular, it has been suggested that tga3 regulates the expression of chitinase-encoding genes, the secretion of the corresponding enzymes and the process of conidiation. Comparative proteome analysis of wild type and disruptants supported this hypothesis, and indicated many changes in the protein profiles of T. atroviride in different interaction conditions with plants and pathogenic hosts.